Analysis of the Use of Photomath Applications to Facilitate Intuitive and Formal Approaches in Mathematics Learning at SMPN 1 Pasir Penyu - Ranisyah, Sanine; Ulandari, Uut; Suripah, Suripah (UIR Press, 2025)
This study aims to analyze the use of the Photomath application as a supporting tool in facilitating an intuitive and formal approach in mathematics learning at SMPN 1 Pasir Penyu. This study uses a qualitative approach by involving 10 students in grade IX.7 of SMP Negeri 1 Pasir Penyu as research subjects. Data collection techniques include giving tests, analysis questions, and documentation. Data analysis is carried out through the process of data reduction, data presentation, and drawing conclusions. The research instruments include description tests, analysis questions, and the Photomath. The results show that Photomath has limitations in helping students complete the description test. Students revealed that this application is less effective because it does not provide audio and video features that can make their understanding easier. In addition, the completion steps provided are considered to be less detailed, so students find it difficult to follow the overall completion process. This finding indicates the need to develop features in the Photomath application to better support optimal mathematics learning.